Short Communication: Polymorphism of Fumarate Hydratase 1 (FUM1) gene associated with nitrogen uptake in oil palm (Elaeis guineensis) - PPB SMART; ZULFIKAR ACHMAD TANJUNG; WIDYARTINI MADE SUDANIA; ANDREE SUNANJAYA KUSNANDAR; ROBERDI; PUJIANTO; CONDRO UTOMO; TONY LIWANG (Society for Indonesian Biodiversity, 2020)
Abstract. Maryanto SD, Tanjung ZA, Sudania WM, Kusnandar AS, Roberdi, Pujianto, Utomo C, Liwang T. 2020. Short Communication: Polymorphism of Fumarate Hydratase 1 (FUM1) gene associated with nitrogen uptake in oil palm (Elaeis guineensis). Biodiversitas 21: 2462-2466.  Nitrogen (N) is an essential element for oil palm vegetative growth and fruit development. Fumarase is known to participate in the tricarboxylic acid (TCA) cycle in the mitochondrial matrix. The FUM gene is required for fumarate accumulation in leaves and necessary to enhance growth under low nitrogen condition. SNPs were obtained in oil palm FUM1 gene based on in silico analysis using local database. The SNP is further verified with Sanger sequencing and qPCR analysis. The genomic DNA of oil palm with high and low efficient to N based on phenotype characters was sequenced using Sanger method. The EgFUM1 gene was located in chromosome 14 and had two SNP positions located in 9.0711 cM and 9.0714 cM. Furthermore, four months oil palm seedlings from three progenies were treated with 30% (N-low) and 100% (control) dosages. Transcription level of EgFUM1 gene was measured using Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) method. The value of fold changes was significantly up-regulated (6.14-fold) on Progeny 1 (high efficient characters); 1.05-fold on Progeny 2 (medium efficient characters); and 1.08-fold on Progeny 3 (low moderate efficient characters) in the leaf. According the result, there was correlation between SNP and transcription level of EgFUM1 gene. Therefore SNP markers of EgFUM1 gene could be used in oil palm selection with potential N uptake efficiency.